2007
DOI: 10.1089/ten.2006.0278
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow–Derived Cultured Mesenchymal Stem Cells Delivered in a Fibrin Spray Accelerate Healing in Murine and Human Cutaneous Wounds

Abstract: The nonhematopoietic component of bone marrow includes multipotent mesenchymal stem cells (MSC) capable of differentiating into fat, bone, muscle, cartilage, and endothelium. In this report, we describe the cell culture and characterization, delivery system, and successful use of topically applied autologous MSC to accelerate the healing of human and experimental murine wounds. A single bone marrow aspirate of 35-50 mL was obtained from patients with acute wounds (n = 5) from skin cancer surgery and from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
528
1
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 699 publications
(570 citation statements)
references
References 27 publications
16
528
1
11
Order By: Relevance
“…As MSCs play a normal role in the wound healing process, they are an obvious candidate for study in this context as opposed to embryonic stem cells or other regenerative sources. Recent studies have outlined some successful approaches to promoting wound healing with MSCs, including autologous bone marrow-derived MSCs in fibrin matrix 52 or, more recently, intramuscular injection of autologous MSCs to improve diabetic wound closure. 54 While some trials have been aimed primarily at safety of MSC use for wound healing, 50 several clinical trials have shown the potential benefit of MSCs for inclusion in wound healing devices, including improved average rate of wound healing and general limb perfusion after treatment 53 and also improved acute wound healing correlating to the number of injected cells.…”
Section: Chronic Skin Woundsmentioning
confidence: 99%
“…As MSCs play a normal role in the wound healing process, they are an obvious candidate for study in this context as opposed to embryonic stem cells or other regenerative sources. Recent studies have outlined some successful approaches to promoting wound healing with MSCs, including autologous bone marrow-derived MSCs in fibrin matrix 52 or, more recently, intramuscular injection of autologous MSCs to improve diabetic wound closure. 54 While some trials have been aimed primarily at safety of MSC use for wound healing, 50 several clinical trials have shown the potential benefit of MSCs for inclusion in wound healing devices, including improved average rate of wound healing and general limb perfusion after treatment 53 and also improved acute wound healing correlating to the number of injected cells.…”
Section: Chronic Skin Woundsmentioning
confidence: 99%
“…Previous attempts to determine the migration and persistence of stem cells in vivo include GFP labeling methods and reporter gene analysis [30][31][32][33]. These studies either noted a lack of stem cell persistence, or experienced time-dependent limits of assay efficacy [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…56 MSCs utilized from more easily accessible sites like adipose tissue found to have a similar healing potential. For instance, in a mouse wound healing model, adipose tissue MSCs loaded on collagen gel resulted in acceleration of the healing, enhancement of the secretion of type I collagen and the extracellular matrix proteins.…”
Section: Preclinical Animal Studiesmentioning
confidence: 99%
“…Falanga et al implanted autologous BM-MSCs loaded in a fibrin spray in five patients with acute wounds from skin cancer surgery and eight patients with chronic, long-standing, non-healing lower extremity wounds. 56 The application of MSCs has stimulated the wound healing process leading to a decrease in size or healing within 20 weeks. It is of note that a strong correlation between the number of cells applied and the subsequent decrease in chronic wound size was noted.…”
Section: Clinical Studiesmentioning
confidence: 99%